HUBUNGAN ASUPAN ZAT GIZI MAKRO DAN FAKTOR LAINNYA TERHADAP STATUS GIZI BALITA DI PUSKESMAS GAMBIR KOTA JAKARTA PUSAT TAHUN 2024 - Kusumaningati, Walliyana; Munawwarah, Sukma (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
The issue examined in this study is the relationship between macronutrient intake, infectious diseases, maternal nutrition knowledge, and feeding patterns in toddlers in the working area of Puskesmas Gambir, Central Jakarta. This research took place in the working area of Puskesmas Kecamatan Gambir, Central Jakarta City, in June 2024. The study used a cross-sectional design with chi-square analysis test using SPSS 25. The subjects of this study were toddlers aged 24–60 months, and the sample consisted of 81 toddlers. Data collection on the nutritional status of toddlers was done using anthropometric measurements (weight & height) with digital scales and stadiometers. Macronutrient intake was assessed using a 2x24 hour food recall sheet, maternal nutrition knowledge was assessed using a maternal nutrition knowledge questionnaire, and feeding patterns were assessed using a child feeding questionnaire. Most toddlers had abnormal nutritional status, and the chi-square test results showed protein intake p=0.477, fat intake p=0.052, carbohydrate intake p=0.678, infectious diseases p=0.448, maternal nutrition knowledge p=0.225, and feeding patterns p=0.279. There was no relationship between macronutrient intake, infectious diseases, maternal nutrition knowledge, and feeding patterns with the nutritional status of toddlers.